The effects of COVID-19 on businesses: Key versus non-key firms - Henry Stemmler (International Labour Organization (ILO), 2022)
This paper analyzes how a specific differentiation by governments throughout the world - whether a sector was deemed "essential" or "key" - affected firm performance. During the COVID-19 pandemic, governments designated specific services as "essential," which allowed firms operating in those sectors to remain (partially) open as well as being granted other preferential treatment. This paper analyses the effects of the key-status, by mapping the countries' lists to the sectoral level, and matching these sectors with firm-level Covid-19 survey data from 27 countries. The findings reveal that, controlling for a rich set of firm-level and sectoral characteristics, firms deemed key less often reported declining sales and demand for their goods or services, and had a smaller number of furloughed workers. Nonetheless, non-key firms were more likely to employ online business activities and to change the main product or service they offered, reflecting the necessity to otherwise adjust to the economic downturn and changes in demand.
Keywords: 330; COVID-19